Analisis Kepuasan Konsumen terhadap Kualitas Produk dan Pelayanan pada Rumah Makan Ayam Geprek Greget - Tarigan, Eli Shylvia Br; Satriawan, I Ketut; Wiranatha, Agung Suryawan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Greget Chicken Geprek Diner is one of the many diners that sell fried chicken. Greget Chicken Geprek Diner strives to maintain product quality and service for customer satisfaction so that customer interest is not reduced. The purpose of this study is to determine the attributes of products and services that are able to satisfy customer needs and provide solutions for improvement. The study was conducted at the Greget Chicken Geprek Diner in Medan. Sampling was done by purposive sampling method and data collection was done by distributing questionnaires and directly to respondents. The analysis was carried out using the Kano method. The study results show on product quality attributes: The promise of being given on time in completing the product, maintaining food hygiene, and consistent chicken size. These three attributes have the “better” (0.8) and “worse” (-0.77) values and are included in the one-dimensional and reverse categories. Attributes of service quality: Waiters prioritize the interests of customers, Management responds to customer complaints, Adequate parking space, Clean rooms, When the payment process is correct or there are no errors, and Waiters respond quickly when called. The six attributes have the highest “better” (0.83) and “worse” (-0.62) scores and are categorized as attractive and one-dimensional. Keyword : Quality of service, customer satisfaction, kano method.